A Case of Neurally Mediated Syncope and Sick Sinus Syndrome Associated With Lung Cancer - Shihomi Kirihara; Shoji Kawakami; Jun-ichiro Nishi (Annals of Internal Medicine: Clinical Cases)
We describe a case of non–small cell lung cancer (NSCLC) associated with recurrent episodes of syncope. During the work-up for syncope, the patient was incidentally found to have a mass in the right upper lobe, which was later diagnosed as NSCLC. Positron emission tomography computed tomography showed metastatic lymphadenopathy of the supraclavicular and paratracheal nodes involving the cardiac branches of the vagus nerve. The patient no longer experienced syncope after starting immunochemotherapy. Considering the rapid and complete remission of syncope after the treatment of lung cancer and the location of metastatic lymphadenopathy, this condition might represent a location-dependent syndrome.